Six-month ground-based water vapour raman lidar measurements over Athens, Greece and system validation - Papayannis, Alexandros D.; Tsaknakis, Georgios; Mamouri, Rodanthi-Elisavet (My University, 2007)
Water vapour is one of the most important greenhouse gases, since it causes about two third of the natural greenhouse effect of the Earth's atmosphere. To improve the understanding of the role of the water vapour in the atmosphere, extensive water vapour profiles with high spatio-temporal resolution are therefore necessary. A ground-based Raman lidar system is used to perform water vapour measurements in Athens, Greece (37.9°N, 23.6°E, 200 m asi.). Water vapour mixing ratio measurements are retrieved from simultaneous inelastic H2O and N2 Raman backscatter lidar signals at 387 nm (from atmospheric N2) and 407 nm (from H2O). Systematic measurements are performed since September 2006. A new algorithm is used to retrieve water vapour vertical profiles in the lower troposphere (0.5-5 km range height asl.). The lidar observations are complemented with radiosonde measurements. Radiosonde data are obtained daily (at 00:00 UTC and 12:00 UTC) from the Hellenic Meteorological Service (HMS) of Greece which operates a meteorological station at the "Hellinikon" airport (37. 54° N, 23.44° E, 15m asl) in Athens, Greece. First results of the systematic intercomparison between water vapour profiles derived simultaneously by the Raman lidar and by radiosondes are presented and discussed.
Keywords: Algorithms; Water vapor; Backscattering; Optical radar